2020
DOI: 10.1007/s00415-020-10235-5
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in maintenance treatment of neuromyelitis optica spectrum disorder

Abstract: Background Treatment of neuromyelitis optica spectrum disorder (NMOSD) has so far been based on retrospective case series. The results of six randomized clinical trials including five different monoclonal antibodies targeting four molecules and three distinct pathophysiological pathways have recently been published. Methods Literature search on clinical trials and case studies in NMOSD up to July 10. 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 149 publications
(190 reference statements)
0
46
0
2
Order By: Relevance
“…According to our current knowledge, DMTs could predispose MS patients to a higher risk of either community-acquired or opportunistic infections ( Grebenciucova and Pruitt, 2017 ; Luna et al, 2020 ). Traditional immunosuppressive treatments and the emerging NMOSD treatments are also associated with an increased risk of infections (viral and bacterial) ( Holmoy et al, 2020 ). Based on this background, it would be reasonable to hypothesize that these therapies may increase the risk of COVID-19 infection predisposing towards a severe infection and worse outcomes ( Brownlee et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to our current knowledge, DMTs could predispose MS patients to a higher risk of either community-acquired or opportunistic infections ( Grebenciucova and Pruitt, 2017 ; Luna et al, 2020 ). Traditional immunosuppressive treatments and the emerging NMOSD treatments are also associated with an increased risk of infections (viral and bacterial) ( Holmoy et al, 2020 ). Based on this background, it would be reasonable to hypothesize that these therapies may increase the risk of COVID-19 infection predisposing towards a severe infection and worse outcomes ( Brownlee et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenic role of NMO-IgG in the presence of human complement is also supported by the results of passive transfer experiments ( 5 , 21 ) and in vivo disease models, where complement inhibition was proven to be beneficial ( 24 ). Moreover, clinical experience also sustains the role of complement activation in disease pathogenesis, since treatment with the monoclonal anti-C5 antibody eculizumab reduced attack frequency, and stabilized or improved neurological disability of patients with NMOSD ( 25 , 26 ). Thus, therapeutic complement inhibition is a promising strategy in the treatment of NMOSD ( 24 , 27 ), and eculizumab has been approved for treating AQP4-IgG positive NMOSD.…”
Section: Introductionmentioning
confidence: 84%
“…Though, IL-6 inhibitors have established themselves as an important class of monoclonal antibodies in the eld of treatment of relapses of NMOSD, the road ahead is long, as the bene ts are only applicable to a large subset of AQP4-Ab seropositive patients leaving behind the important hurdle to nd a drug that can impact the disease course of AQP-4 Ab seronegative groups. 10 Our meta-analysis has several strengths. We have systematically collected all evidence including real-world data and RCTs for the e cacy and safety of IL-6 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…are being widely used and studied. 10 IL-6 inhibitors like Tocilizumab and Satralizumab, are now being considered as good options for treatment of NMO/NMOSD and potential therapeutic effects of two anti-IL-6 agents Tocilizumab and Satralizumab have been investigated via clinical trials and have shown promising results in the treatment of active NMOSD case, however, summarized data is lacking. 11 To establish IL-6 inhibitors drugs as e cacious and tolerated treatment options in the management of NMO/NMOSD, this meta-analysis is done with the aim of nding the combined effect size of their e cacy and safety from real-world studies.…”
Section: Introductionmentioning
confidence: 99%